2023
DOI: 10.3389/fendo.2023.1134208
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple blood metals with thyroid function in general adults: A cross−sectional study

Abstract: IntroductionThyroid function has a large impact on humans’ metabolism and is affected by iodine levels, but there is a scarcity of studies that elucidate the association between thyroid function and other elements.MethodsWe performed a cross-sectional study on 1,067 adults to evaluate the associations of the common essential metals with thyroid function in adults living in an iodine-adequate area of China. Serum free thyroxine (FT4), free triiodothyronine (FT3), thyroid stimulating hormone (TSH), and blood met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(56 reference statements)
0
3
0
1
Order By: Relevance
“…We did not find a significant association between Mg and thyroid function biomarkers, and the nutrient mixture model did not show that Mg makes a great contribution to the overall effect, which is consistent with the findings from previous studies. Cross-sectional studies found no significant association between Mg and thyroid hormones [37]. Only a severely low serum Mg level is associated with an increased risk of hypothyroidism [38].…”
Section: Effects Of Ca and Mg On Thyroid Functionmentioning
confidence: 97%
“…We did not find a significant association between Mg and thyroid function biomarkers, and the nutrient mixture model did not show that Mg makes a great contribution to the overall effect, which is consistent with the findings from previous studies. Cross-sectional studies found no significant association between Mg and thyroid hormones [37]. Only a severely low serum Mg level is associated with an increased risk of hypothyroidism [38].…”
Section: Effects Of Ca and Mg On Thyroid Functionmentioning
confidence: 97%
“…The levels of FT3, FT4, TSH, thyroid peroxidase antibodies (TPOAb), and thyroglobulin antibody (TgAb) in the serum were analyzed using the Microparticle Enzyme Immunoassay (MEIA) technique on the UniCel Dxi 800 Access instrument (Beckman Coulter, USA). We used the normal reference ranges for thyroid function and thyroid antibodies recommended by manufacturers: TSH (0.56-5.91 pmol/L), FT3 (3.53-7.37 pmol/L), FT4 (7.98-16.02 pmol/L), TPOAb (0-9 IU/ mL), and TgAb (0-4.9 IU/mL) (17,18). Fasting plasma glucose (FPG), 2-h postprandial plasma glucose (PPG), creatinine, serum total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were measured by the automatic biochemical analyzer AU5831 (Beckman Coulter, USA).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…В исследовании, проведенном в Китае, Yanshi Ye и соавт. выявили связи следующих МЭ в крови: железа, цинка, меди, марганца между собой и с функцией ЩЖ [17]. Полученные нами данные согласуются с результатами исследования, проведенного в Алжире, где у 220 взрослых также выявили отрицательную связь между уровнем селена и показателями титра АТ-ТПО [18].…”
Section: сопоставление с другими публикациямиunclassified